On‐farm Performance and Farmers' Perceptions of DroughtTEGO‐Climate‐Smart Maize Hybrids in Kenya. (1st November 2019) - Obunyali, Caleb Omwibali; Karanja, James; Oikeh, Sylvester Ojo; Omanya, Gospel Oluoch; Mugo, Stephen; Beyene, Yoseph; Oniang'o, Ruth Khasaya
Abstract : Maize ( Zea mays L.) productivity in the sub‐Saharan Africa is constrained by biotic and abiotic stresses that reduce yield. In the region, one of the most serious abiotic factor is frequent intermittent droughts, which has been attributed to climate change. The purpose of this paper was to use on‐farm demonstration studies and farmer field days to demonstrate new drought mitigation technology and provide information on how small farmers can reduce yield losses. A total of 4814 demonstration plots of 39 DroughtTEGO maize hybrids and 19 commercial check hybrids were established in 17 counties across the low‐to‐mid‐altitude maize‐growing agroecologies of Kenya between 2015 and 2017. A total of 246 field‐day workshops were conducted. Combined analyses across years and locations showed that top five DroughtTEGO hybrids increased maize yields 33 to 54% (5.5–6.3 Mg ha −1 ) relative to conventional hybrids. The highest yield advantage of DroughtTEGO hybrids over commercial checks was observed in the drier lower eastern region in Kenya. Farmers particularly women, preferred the DroughtTEGO hybrids because of the stay‐green character, whiteness of flour (milling quality), root lodging resistance, drought‐tolerance and shelling percentage. Results from this study suggested that smallholder farmers can reduce the impact of drought by seeding drought‐tolerant maize hybrids. Core Ideas High yields and farmer‐preferred traits determine adoption of new varieties. Conducting on‐farm demonstrations can overcome adoption barriers. Planting of drought‐tolerant hybrids mitigates drought stress for smallholder‐farmers.